HGF/c-Met: A Key Promoter in Liver Regeneration - Zhao, Yang; Ye, Wenling; Wang, Yan-Dong; Chen, Wei-Dong (Frontiers in Pharmacology, 2022)
Hepatocyte growth factor (HGF) is a peptide-containing multifunctional cytokine that acts on various epithelial cells to regulate cell growth, movement and morphogenesis, and tissue regeneration of injured organs. HGF is sequestered by heparin-like protein in its inactive form and is widely distributed in the extracellular matrix of most tissues. When the liver loses its normal mass, volume, or physiological and biochemical functions due to various reasons, HGF binds to its specific receptor c-Met (cellular mesenchymal-epithelial transition) and transmits the signals into the cells and triggers the intrinsic kinase activity of c-Met. The downstream cascades of HGF/c-Met include JAK/STAT3, PI3K/Akt/NF-κB and Ras/Raf pathways, thereby affecting cell proliferation, growth and survival. HGF has important clinical significance for liver fibrosis, hepatocyte regeneration after inflammation and liver regeneration after transplantation. And the development of HGF as a biological drug for regenerative therapy of diseases, that is, clinical trials using recombinant human HGF protein to treat diseases are underway. In this review, we will report and discuss recent findings about the functions of HGF signaling in liver regeneration.